Three-dimensional Computed Tomographic Reconstruction of the Carotid Artery: Identifying High Bifurcation. Issue 2 (February 2015) - McNamara, J.R.; Fulton, G.J.; Manning, B.J.
Abstract : Objective: To investigate variability in the level of bifurcation relative to other anatomical landmarks on computed tomography (CT) and to develop an objective and reproducible technique for identifying patients with a high carotid bifurcation who might therefore be at greater risk of operative complications. Methods: This was a retrospective cross-sectional, imaging study. A series of 86 nonselected consecutive CT carotid angiograms (172 arteries) were analysed. Using three-dimensional reconstructive software, the curved length (CL) of the internal carotid artery (ICA) and the straight-line distance (SLD) from the bifurcation to the base of skull was measured for 140 carotid arteries. The tortuosity index (TI) of each ICA was calculated by dividing CL by SLD. The relationship of the bifurcation to eight anatomical landmarks in the neck was assessed in order to identify a landmark that could act as a surrogate marker of high carotid bifurcation. The landmarks examined were the angle of mandible, greater horn of hyoid, body of hyoid, upper margin of thyroid cartilage, cervical vertebrae, mastoid process, sternoclavicular joint, and sternal notch. Results: The median curved length of the ICA was 80.4 mm (range 58.0–129.0 mm). The median distance of bifurcation from the base of the skull was 72.7 mm (range 58.1–98.1 mm). There was excellent interobserver agreement in measuring SLD, with an intraclass correlation coefficient of 0.993 ( p = .00). The median tortuosity index was 1.12 (range 1.01–1.64). Distance from the mastoid process had the greatest correlation with high bifurcation; Pearson's correlation coefficient of 0.894 (two-tailed p = .00). Bifurcations within 5 cm of the mastoid process are likely to be in the highest quartile (82.9% sensitive, 80.1% specific). Conclusions: Measuring the distance of carotid bifurcation from the base of the skull (SLD), a measure previously not well defined, may be useful in predicting difficult neck dissection and endarterectomy. A distance from mastoid of ≤ 5 cm may also alert the surgeon to potential difficulties.